2016
DOI: 10.5194/isprs-archives-xli-b2-675-2016
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Visual Interpretation of Satellite Data

Abstract: ABSTRACT:Millions of people of all ages and expertise are using satellite and aerial data as an important input for their work in many different fields. Satellite data are also gradually finding a new place in education, especially in the fields of geography and in environmental issues. The article presents the results of an extensive research in the area of visual interpretation of image data carried out in the years 2013 -2015 in the Czech Republic. The research was aimed at comparing the success rate of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
0
16
0
6
Order By: Relevance
“…It is widely known that appropriate false color composite imagery can provide a great amount of information for the interpreter as it can considerably improve visual perception. A study by Svatonova [124] showed that non-expert image interpreters can interpret false color satellite imagery very well. Specifically, Svatonova [124] recommended providing false color imagery alongside true color imagery in web mapping services to enhance the image interpretation performance of the non-experts.…”
Section: Collecting Data On Trees Through Crowdsourcingmentioning
confidence: 99%
See 4 more Smart Citations
“…It is widely known that appropriate false color composite imagery can provide a great amount of information for the interpreter as it can considerably improve visual perception. A study by Svatonova [124] showed that non-expert image interpreters can interpret false color satellite imagery very well. Specifically, Svatonova [124] recommended providing false color imagery alongside true color imagery in web mapping services to enhance the image interpretation performance of the non-experts.…”
Section: Collecting Data On Trees Through Crowdsourcingmentioning
confidence: 99%
“…A study by Svatonova [124] showed that non-expert image interpreters can interpret false color satellite imagery very well. Specifically, Svatonova [124] recommended providing false color imagery alongside true color imagery in web mapping services to enhance the image interpretation performance of the non-experts. Hence, to collect spatial data (i.e., tree locations) and attribute data (i.e., tree basic geometrical property) about ITCs through crowdsourcing approach (i.e., tree identification, ITC identification) in this study, true color R-G-B and false color NIR1-R-G composites of the aforementioned VW3 imagery were produced for the test plot and provided to the volunteers through the developed platform.…”
Section: Collecting Data On Trees Through Crowdsourcingmentioning
confidence: 99%
See 3 more Smart Citations